THE EFFECT OF HEATING TIME TO THE CONTENT OF PIGMENTS AND VITAMIN A IN CASSAVA (Manihot esculenta Crantz) AND CEARA-RUBBER (Manihot glaziovii Muell. Arg) LEAVES - Madalena Madalena; Heriyanto Heriyanto; Susanti Pudji Hastuti; Leenawaty Limantara (Universitas Gadjah Mada, 2007)
Cassava and ceara-rubber leaves are leavy vegetables that can not be consumed in raw form because they contained cyanide, therefore cooking process is needed to remove the cyanide. However cooking process cause the changes of the content of pigments and vitamin A. The aims of the research are to know and to compare the effect of heating time to the content of pigments and vitamin A in cassava and ceara-rubber leaves. Content of chlorophyll and carotenoid was analized base of Porra and Lichtenthaler equations, respectively, while pheophytin content was analyzed base on HPLC. The result shown that the content of chlorophylls, carotenoids and vitamin A of cassava and ceara-rubber leaves were reduced, while the content of pheophytin was increased during heating. Pheophytin was the main product degradation of chlorophyll during heating of cassava and ceara-rubber leaves.